2020
DOI: 10.12659/ajcr.920016
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Salicylate Toxicity Presenting with Acute Focal Neurologic Deficit in a 61-Year-Old Woman with a History of Stroke

Abstract: Unknown ethiology Background:Over-the-counter medications that contain aspirin are widely used, and patients generally regard them as safe. However, the side effects of salicylate toxicity can be severe, and delay in the diagnosis may increase the risk of mortality. Neurologic symptoms are a common presenting feature of salicylate toxicity in the elderly, and their recognition may allow earlier diagnosis. This report is of a case of a 61-year-old woman who presented with acute focal neurologic deficit associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Exceptionally, it was reported that damage to the peripheral acoustic nerves and auditory cortex could occur [6]. In another case with previous cerebral infarction, left hemiparesis recurred following chronic salicylate ingestion, without fresh cerebral infarction on MRI [7].…”
Section: Discussionmentioning
confidence: 99%
“…Exceptionally, it was reported that damage to the peripheral acoustic nerves and auditory cortex could occur [6]. In another case with previous cerebral infarction, left hemiparesis recurred following chronic salicylate ingestion, without fresh cerebral infarction on MRI [7].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] However, their side effects at high dosages limit their potential application in cancer therapy. [19][20][21] To overcome these limitations, nanotechnology-based drug delivery systems have been exploited for tumor-selective aspirin delivery. [22][23][24][25] Inorganic nanomaterials, including gold nanorod, have been used to deliver aspirin through π-π interaction, with the resultant nanoaspirin reducing inflammatory responsiveness of tumor tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo relatórios dos Centros de Controle de Intoxicações dos Estados Unidos, em 2007, foram relatados 79.000 casos de ingestão abusiva de ibuprofeno no país. Além disso, foi observado que 40.000 americanos são expostos aos salicilatos anualmente; estes estão entre os medicamentos mais antigos que são amplamente utilizados até hoje e embora sejam considerados seguros pelos pacientes, podem resultar em intoxicações fatais, principalmente em idosos (BOWERS et al, 2019;DELANEY et al, 2020). Dessa forma, é imprescindível a compreensão do mecanismo de ação dos anti-inflamatórios não esteroides.…”
unclassified